THE PRACTICAL MOBILIZATION OF TRADITIONAL KHOREZMIAN MAKOMS (MUSICAL TUNES) (American Journal of Research in Humanities and Social Sciences, 2023)
The art of Khorezm is ancient, as we may know it from its old musical notes which have survived until today. In particular, the performance of makoms is widely developed in Khorezm. Besides the Khorezmian six-and-a-half makom and dutor makom and surna makom, there are also traditional makoms, which are currently being restored and compiled. This article contains the information about the people who contributed to conveying Khorezmian makoms up to the present day